Efektivitas Program Tahfidz 30 JUZ Di SMP Negeri Tahfidz Madani Rokan Hulu Riau - Gozali, Gozali (STAI Publisistik Thawalib Jakarta, 2023)
The aim of the study was to describe the process of implementing the tahfidz 30 jus program which was carried out at the Tahfidz Madani Rokan Hulu Riau Public Junior High School. Qualitative research methods with an analytical study approach. Data collection techniques by interviewing 1 principal, 4 teachers, and 4 students, documentation, and observation. Data analysis with reduction, data display, and conclusion. Data validity technique with source and technique triangulation. The results showed: (1) planning the tahfidz program by determining the tahfidz daily program. (2) implementing the tahfidz program with selection, reading, and memorizing tests before entering school. (3) the aim of the tahini program, first is that students can memorize the Al-Qur'an according to the provisions. The second purpose of educators is to monitor and assess students' memorization. The three objectives of the principal are to supervise the implementation of tahfidz in schools. (4) the tahfidz program through the implementation of memorizing deposits, the amount of the deposit, as well as the implementation of Al-Qur'an memorization tests.